THE IMPACT OF FIRM SIZE, ACCOUNTING CONSERVATISM ON EARNINGS QUALITY MODERATED BY INDEPENDENT COMMISSIONER - Hastuti, Rini Tri; Lusiana, Lusiana (Graduate Program of Universitas Tarumanagara, 2023)
This research was conducted with the aim of obtaining real information about earnings quality which is influenced by firm size variable and accounting conservatism with moderated variable, namely independent commissioners in manufacturing companies on the IDX for the 2018-2020 period. Descriptive research design with quantitative data properties where the data used in this study were measured and presented in the form of numbers. The sampling technique used is purposive sampling with a panel data approach followed by 153 sample data from 51 companies for 3 years, from 2018-2020. In addition, in this study, the data collected to test the hypothesis using the panel data regression model was processed using EViews version 11. The results obtained from this test showed that accounting conservatism had no significant effect on earnings quality. While the size of the company has a significant impact on earnings quality. Furthermore, the moderating variable is the independent commissioner in this study cannot moderate the effect of earnings quality and firm size but can moderate the effect of accounting conservatism on earnings quality